Policy Implementation of Child Welfare Institutions in Fulfilling Children’s Rights - Alwan Nabil; Fentiny Nugroho (LifeSciFi, 2026)
The fulfillment of neglected children’s rights remains a major challenge in Indonesia’s social welfare system. This study critically examines the implementation of social policies at Child Welfare Institutions (Lembaga Kesejahteraan Sosial Anak/LKSA) in fulfilling the rights of neglected children in Jember Regency. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. Findings reveal a significant implementation gap, where policies are reduced to administrative practices rather than serving as instruments for fulfilling children’s rights. Although the regulatory framework is relatively comprehensive, its normative nature, lacking operational technical standards, encourages the dominance of implementers’ discretion and results in varied implementation. Furthermore, problematic interactions between inconsistent communication, resource constraints, actor dispositions, and fragmented bureaucratic structures reinforce the ineffectiveness of the policy. These conditions indicate a weak policy design in anticipating the complexities of implementation. Therefore, a policy reorientation is needed, shifting from administrative compliance toward a rights-based approach through the strengthening of operational standards, actor capacity, and institutional integration.